The Influence of AudioVisual Media on Ecological Intelligence and Critical Reasoning Ability in Class V Social Studies Learning at SD Negeri 1 Kabunderan, Purbalingga Regency - Eko Waluyo Budi Utomo (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
Learning involves the active interaction of individuals with their environment, leading to behavioral changes. Effective learning encompasses being student-centered, promoting educational interaction, creating a pleasant learning atmosphere, using various methods, providing suitable materials, and ensuring a conducive environment and supporting facilities. This study aimed to improve critical thinking skills about the environment in elementary social studies by applying audio-visual learning media. Using a descriptive method with a quantitative approach, the research involved 32 grade V students from SD Negeri 1 Kabunderan, Purbalingga Regency. The results showed a significant relationship between the audio-visual learning model and ecological intelligence (p = 0.038) and between the audio-visual learning model and critical reasoning ability (p = 0.037). These findings indicate that audio-visual media effectively enhances both ecological awareness and critical thinking skills in elementary social studies learning.